Exploring Young and Green Entrepreneurship in Indonesia: An Introduction - Gunawan, Janti; Fraser, Kym (Journal of Asian Business Strategy, 2017)
This study was undertaken to better understand how to promote young and green entrepreneurship in Indonesia, where institutional support is limited. A large proportion of the Indonesian population is young but business start-ups are low and youth unemployment is high. Gaps in institutional development, economic growth, social and environmental wellbeing are all massive challenges for the country, which also faces a huge geographical spread of its population. Entrepreneurship is now being promoted by the government as a policy direction to help reduce some of the economic and social inequities which exist. Global organisations, such as ILO, OECD and UN, are also actively encouraging young entrepreneurship and eco-business as sustainable options for many social, economic and environmental challenges. This study proposes a relationship model between entrepreneurial characteristics, institutional environment and young entrepreneurs’ innovativeness. While the response rate to the web-based survey was too low to test the proposed hypotheses, the paper does provide a meaningful introduction to this important topic, along with a comprehensive summary of constructs and measures of variables to encourage further research and to assist future researchers.